Accuracy of Pooled-Cohort Equation and SCORE cardiovascular risk calculators to identify individuals with high coronary atherosclerotic burden – implications for statin treatment. Issue 7 (November 2016) - Tralhão, António; Ferreira, António M.; Gonçalves, Pedro de Araújo; Rodrigues, Rita; Costa, Cátia; Guerreiro, Sara; Cardim, Nuno; Marques, Hugo
Abstract : Background: Different cardiovascular risk calculators and risk-based thresholds for initiating statin therapy are currently in use. Using coronary computed tomography angiography, we sought to compare the Pooled-Cohort Equation [atherosclerotic cardiovascular disease (ASCVD) score] with the Systematic COronary Risk Evaluation (SCORE) in the identification of patients with high coronary atherosclerotic burden. Methods: In a single-center prospective registry of patients undergoing coronary computed tomography angiography, we identified individuals aged 40–75 years without diabetes or known cardiovascular disease. Cardiovascular risk and eligibility for statin therapy were determined individually on the basis of the two calculators and the guidelines that endorse them. Coronary atherosclerotic burden was assessed by coronary calcium score, presence of stenosis greater than or equal to 50%, and several measures of plaque severity and extension. Results: In the 327 patients assessed (181 men, mean age 59±9 years), the median SCORE and ASCVD values were 2.6 and 9.7%, respectively. Compared with SCORE, the ASCVD calculator showed greater discriminative power to identify patients with calcium score greater than or equal to 300 [ C -statistic 0.74, 95% confidence interval (CI) 0.67–0.82 vs. 0.69, 95% CI 0.61–0.78, P =0.008] and showed a trend toward better identification of patients with obstructive stenosis ( C -statistic 0.72, 95% CI 0.64–0.80 vs. 0.68, 95% CI 0.60–0.76, P =0.053). The proportion of statin-eligible patients would be higher with the SCORE-based criteria, particularly among individuals with little or no detectable coronary atherosclerosis. Conclusion: The SCORE calculator seems to be less discriminative than the ASCVD equation in identifying patients with high atherosclerotic burden. Current SCORE-based criteria would assign statin therapy to a larger proportion of patients with low-risk features, which could result in a lower yield of cholesterol-reducing strategies.